Testing the right skill: Evidence to support testing translation ability - Brooks, Rachel Lunde; Brau, Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2018)
In the United States Government (USG), language-test scores in the various skills are defined by reference to the Interagency Language Roundtable (ILR) Skill Level Descriptions (SLDs). The ILR SLDs for Translation Performance state that reading the source language (SL) and writing the target language (TL) are prerequisites for translating but add that there is a prerequisite third skill, termed “congruity judgement”. Since the Language Testing and Assessment Unit (LTAU) of the Federal Bureau of Investigation (FBI) uses the ILR as the basis for its translation testing, it has conducted several studies on test results to discover the interconnection, if any, of these requisites.